Modelling the behavioural component of the emergent parallel processes of working with graph databases using Petri net-tools. Issue 6 (2nd November 2021) - Velykodniy, Stanislav; Burlachenko, Zhanna; Zaitseva-Velykodna, Svitlana
Abstract : The article focuses on the transformation of the behavioural UML diagrams modelled by the authors, which reflect the emergent manifestations of the life cycles of working with graph databases (GDB), to models in the form of Petri nets. Such a transformation process was carried out for the diagrams of objects, states, sequences, and activities. The extended UML 2.5 notation and Enterprise Architect 14.0 CASE tool were used in the formation of the project architecture. Modelling of the emergent parallel processes of working with GDBs in the form of a Petri net might initially seem to make the sequence more complicated for the designer to perceive than while using UML modelling, in which the relationships between entities on a diagram are obvious to the user. Conversely, the representation of behavioural models in the form of Petri nets facilitates the reflection of other important emergent points, in particular, by demonstrating objects relationship, dynamic information updates, components, or other necessary information concerning parallel GDB design.